On the Peristaltic Transport of a Micropolar Fluid - DEY, K.N.; PORIA, S.; MAZUMDAR, H.P. (Engineering Transactions, 2005)
In this paper, we study some characteristics of the peristaltic motion of an incompressible micropolar fluid through a circular cylindrical tube. Many authors have investigated the peristaltic motion of non-Newtonian or viscoelastic fluid through a channel or tube due to the relevance of peristaltic action in both mechanical and physiological situations. For example, peristaltic mechanism may be involved in vasomotion of small blood vessels. Here the microstructural effects on the pressure rise, average flow and friction force are investigated.